2013
DOI: 10.1136/sextrans-2013-051302
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a routine HIV testing policy in an acute medical setting in a UK general hospital: a cross-sectional study: Table 1

Abstract: Our experience shows that routine opt-out testing can be delivered and sustained by general medical staff in an AMU with no money spent other than laboratory processing of the test. We believe that success and sustainability of this policy is due to the high level of commitment from and ownership by the AMU staff, particularly nurses. Ongoing support and motivation from the HIV team has facilitated the delivery of this policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 7 publications
(4 reference statements)
3
30
0
Order By: Relevance
“…Similar reported initiatives in MAU across the UK have also had mixed success with uptake of HIV testing ranging from 22% in Northern England3 to 28% and 32.5% in other London MAU's 4 5. This is in contrast to routine HIV testing in other areas of our own hospital, where better testing rates have been seen in the emergency department (30% uptake)6 and critical care department (52%) 7.…”
supporting
confidence: 53%
“…Similar reported initiatives in MAU across the UK have also had mixed success with uptake of HIV testing ranging from 22% in Northern England3 to 28% and 32.5% in other London MAU's 4 5. This is in contrast to routine HIV testing in other areas of our own hospital, where better testing rates have been seen in the emergency department (30% uptake)6 and critical care department (52%) 7.…”
supporting
confidence: 53%
“…HIV testing uptake, coverage and linkage to care As shown in Table 1, the HIV testing uptake ranged from 53% to 84%. In the UK, HIV test uptake in EDs (62-63%) [26,28], was lower than AMUs (70-84%), [26,30,32]. In the US, the uptake levels in EDs ranged from 53% to 75% [36,37].…”
Section: Results Of Individual Studiesmentioning
confidence: 96%
“…The high‐level commitment and motivation of medical staff (especially nurses) offering HIV tests was identified in two UK‐based studies as a facilitator of offering HIV testing . Moreover, Rayment et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips et al 1 found that a third of inpatients had HIV tests following implementation of a routine HIV testing policy at Croydon University Hospital. We recently found similar rates of HIV testing in young women in the community in our medical student research projects.…”
mentioning
confidence: 99%